2011
DOI: 10.1016/j.pain.2010.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Identifying prescription opioid use disorder in primary care: Diagnostic characteristics of the Current Opioid Misuse Measure (COMM)

Abstract: The Current Opioid Misuse Measure (COMM), a self-report assessment of past-month aberrant medication-related behaviors, has been validated in specialty pain management patients. The performance characteristics of the COMM were evaluated in primary care (PC) patients with chronic pain. It was hypothesized that the COMM can identify patients with prescription drug use disorder (PDD). English-speaking adults awaiting PC visits at an urban, safety-net hospital, who had chronic pain and had received any opioid anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 23 publications
1
94
0
4
Order By: Relevance
“…Esta escala ayuda a identificar a aquellos pacientes tratados con opioides que los estań usando de forma incorrecta; fue validada en pacientes tratados con opioides durante una media de 5,7 años (37,20). La escala COMM es una autoevaluación breve desarrollada con el asesoramiento de un grupo de expertos en dolor y adicciones.…”
Section: Seguimiento Del Paciente En Tratamiento Opioideunclassified
“…Esta escala ayuda a identificar a aquellos pacientes tratados con opioides que los estań usando de forma incorrecta; fue validada en pacientes tratados con opioides durante una media de 5,7 años (37,20). La escala COMM es una autoevaluación breve desarrollada con el asesoramiento de un grupo de expertos en dolor y adicciones.…”
Section: Seguimiento Del Paciente En Tratamiento Opioideunclassified
“…7 In 2 studies, the sensitivity and specificity were maximized with a cutoff score of $9 of 68, 6,7 whereas a higher cutoff score of $13 of 68 maximized these values in a third study. 41 Meltzer et al 41 also found higher COMM scores in patients with chronic pain who had a prescription drug use disorder than in those who did not have the disorder, supporting the construct validity of the instrument.…”
Section: Current Opioid Misuse Measure (Comm)mentioning
confidence: 92%
“…A cutoff score of $9 yields a sensitivity of 71% and a specificity of 71% (same criterion). Meltzer et al 41 Primary care patients with chronic pain (N = 238) Significantly higher COMM score in patients with prescription drug use disorder than those without. ROC analysis yielded an AUC of .84 (criterion is DSM-IV prescription drug use disorder).…”
Section: Patient-reported Instruments: Nonspecificmentioning
confidence: 99%
See 1 more Smart Citation
“…Early interventions can prevent the problem from worsening, and attention to the risk factors highlighted herein could compliment or refine the use of tools that screen for opioid addiction (Adams et al, 2004;Fleming, Balousek, Klessig, Mundt, & Brown, 2007;Meltzer et al, 2011) in order to increase the currently low attention (Haller & Acosta, 2010) paid to early detection of OAUD. Haller and Acosta (2010) suggest using psychiatric or substance abuse consultants in order to help identify persons (adolescents in schools, in this case) who may be at greatest risk for OAUD, and then offering brief behavioral interventions or on-site therapy in order to prevent problem occurrence or escalation.…”
Section: Opioid Analgesic Use Disordersmentioning
confidence: 99%